Modelos de preferências para definição da importância relativa dos critérios de avaliação de desempenho funcional de uma IFES - Souza, Francisco Gultierrez Lima (2021)
The Federal Constitution of 1988 encouraged the demanding for quality public services by the population, reducing waste and valuing users-citizens. Considered a strategic management process of utmost importance, the performance evaluation proposes to monitor, in an organized and structured way, the performance of employees in the work environment. Thus, this study aims to propose a preference model for the performance evaluation process in a federal institution of higher education, located in the city of Sobral/CE, using multicriteria models to support the decision, AHP and Promethee. The theoretical basis discusses the management of people in public administration, as well as the legal aspects and methods of performance evaluation, besides presenting theoretical concepts about multicriteria decision methods. This is a descriptive research, with a quantitative approach. As for the technical procedures of data collection, it is classified as documentary, field study and case study. As a final result, it was possible to contextualize the functional evaluation process of the institution above mentioned, through its historical path, its challenges and its current method. With the application of the MMAD methods, it was possible to verify that the vast majority of evaluative members participating in the research attributed different marks to the evaluative factors, in contrapoint to the current model where the evaluative factors have the same importance, and to the decision-makers. The decision-making Working Group, which does not directly contribute to the current model, was considered as the second most important in 3 evaluation groups (Groups A and B, E and FG) and the first in the other 2 (C and D and CD). It was suggested the use of the weighted average to achieve the necessary scores to achieve the final score of the evaluation process in counterpoint to the current model that uses a conversion matrix intuitively. In the end, it was possible to structure a calculation matrix, based on mathematical models, on the preferences of decision makers and, consequently, more aligned with reality.